REGULATORY AND LEGAL FOUNDATIONS FOR ENSURING THE ECONOMIC STABILITY OF SERVICE SECTOR ENTITIES IN THE REPUBLIC OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the legal and regulatory framework ensuring the economic stability of service sector entities in the Republic of Uzbekistan. It analyzes national legislation, regulatory policies, and institutional mechanisms that support sustainable business operations. The study highlights the role of government oversight, fiscal measures, and strategic planning in promoting sector resilience. Key challenges affecting economic stability, including market fluctuations and legal inconsistencies, are identified. The article provides comparative insights from international best practices. Emphasis is placed on the integration of regulatory compliance with economic performance. The research evaluates how legal reforms influence operational efficiency and financial sustainability. Case studies of service enterprises illustrate practical applications of the regulatory framework. Policy recommendations are proposed to strengthen governance and risk management.